2020
DOI: 10.1186/s12931-020-01461-6
|View full text |Cite
|
Sign up to set email alerts
|

Endotrophin, an extracellular hormone, in combination with neoepitope markers of von Willebrand factor improves prediction of mortality in the ECLIPSE COPD cohort

Abstract: Background: Lung epithelial damage, activation of the wound healing cascade, and remodeling of the extracellular matrix (ECM) play a major role in chronic obstructive pulmonary disease (COPD). The pro-peptide of type VI collagen has been identified as the hormone endotrophin. Endotrophin has been shown to promote fibrosis and inflammation, whereas von Willebrand factor (VWF) is a crucial part of wound healing initiation. Here, we assessed the released and activated form of VWF and endotrophin, the pro-peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Further studies in humans have substantiated this link. Yoldemir et al found endotrophin significantly associated with insulin resistance and upregulated in overweight individual [41] and several clinical studies have found endotrophin elevated in fibrotic conditions where it is produced by fibroblasts [12,13,15,16]. This correlates well with our findings where endotrophin levels were associated with both fibrotic and obesity-related clinical variables and chronic diseases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further studies in humans have substantiated this link. Yoldemir et al found endotrophin significantly associated with insulin resistance and upregulated in overweight individual [41] and several clinical studies have found endotrophin elevated in fibrotic conditions where it is produced by fibroblasts [12,13,15,16]. This correlates well with our findings where endotrophin levels were associated with both fibrotic and obesity-related clinical variables and chronic diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In animal models, endotrophin has been shown to be involved in several biological processes, such as fibrosis, inflammation, angiogenesis, insulin resistance and epithelial-mesenchymal transition (EMT) [10,11]. In humans, endotrophin has been linked to chronic kidney disease (CKD) [12,13], breast cancer [14], chronic obstructive pulmonary disease (COPD) [15,16], diabetes [17,18] and death [19].…”
Section: Introductionmentioning
confidence: 99%
“…Low concentrations of interleukin-15, a pleiotropic cytokine that induces proliferation of natural killer cells, and high concentrations of interleukin-8, a cytokine targeting neutrophils, have been associated with an increased risk of exacerbations [8]. High levels of endotrophin and von Willebrand factor as well as other markers of epithelial repair, alveolar destruction, and endothelial dysfunction have been correlated with higher morbidity and mortality in COPD [53 ▪ –56 ▪ ]. Low-serum IgG and free light chain levels have been linked to a higher risk of exacerbation and hospitalization, which suggests a potential role for intravenous immunoglobulin administration in COPD patients with recurrent exacerbations [57 ▪ –59 ▪ ].…”
Section: Biomarkersmentioning
confidence: 99%
“…The biological role of endothrophin in cancer is related to epithelial-to-mesenchymal transition and tumor fibrosis. Endothrophin is highly expressed in CAFs and is prognostic in a range of fibrotic diseases, including liver, lung, kidney, and skin fibrosis (31)(32)(33)(34)(35)(36). Understanding how collagens and collagen fragments actively bind and regulate immune receptors, in addition to functions described here, will be critical to link cancer matrix biology and immune oncology.…”
mentioning
confidence: 91%